Critical Analysis of the Judge's Considerations in the Mesuji Religious Court Decision No. 7/Pdt.P/2023/PA.Msj - Dinisa, Daffa Ul-Haq; Edi, Relit Nur; Putra, Muhammad Haidir Syah (Journal of Law, Politic and Humanities, 2025)
This research is a critical study of the process and decision of the Mesuji Religious Court regarding the application for the determination of guardianship rights for a minor child named Abid Fariyanto bin Abdul Gani. The application was filed by Kabul Wakidi bin Rasiman and Sumarni binti Sutariyo on March 21, 2023. The panel of judges granted the application, appointed both applicants as responsible guardians, and imposed court costs of Rp 520,000. The judge's considerations were based on the facts of the child’s parents’ divorce, the absence of the father whose whereabouts are unknown since 2013, and the death of the biological mother in January 2023. The certificate of unknown whereabouts issued by the Village Head does not have the same force as a court order regarding supernatural status. Revocation of guardianship rights is a serious decision that must be made by a court decision, considering various factors in the best interests of the child, such as neglect, abuse of authority, and other dangerous conditions.